Corticosterone induces obesity partly via promoting intestinal cell proliferation and survival - Wang, Guanhao; Li, Shuanqing; Li, Yingqi; Zhang, Meihui; Xu, Ting; Li, Tianming; Cao, Lining; Lu, Jianfeng (Frontiers in Endocrinology, 2023)
Introduction A vicious cycle ensues whereby prolonged exposure to social stress causes increased production of glucocorticoids (GCs), leading to obesity even further. Understanding the role of GCs, the key element in the vicious circle, might be helpful to break the vicious circle. However, the mechanism by which GCs induce obesity remains elusive. Methods Corticosterone (CORT) was administered to mice for 8 weeks. Food and water intake were recorded; obesity was analyzed by body-weight evaluation and magnetic resonance imaging (MRI); intestinal proliferation and survival were evaluated by H&E staining, EdU-progression test, TUNEL assay and immunofluorescence staining of Ki67 and CC3; RNA-seq was performed to analyze transcriptional alterations in small intestines and livers. Results Chronic CORT treatment induced obesity, longer small intestines, hepatic steatosis and elevated levels of serum insulin and leptin in mice; CORT-treated mice showed increased cell proliferation and decreased apoptosis of small intestines; RNA-seq results indicate that differentially expressed genes (DEGs) were enriched in several cell growth/death-associated signaling pathways. Discussion Herein we find that administration of CORT to mice promotes the proliferation and survival of intestinal cells, which might contribute to the longer small intestines and the elongated intestinal villi, thus leading to increased nutrient absorption and obesity in mice. Understanding CORT-induced alterations in intestines and associated signaling pathways might provide novel therapeutic clues for GCs or stress-associated obesity.